Parole migranti in italiano - Ferrari, Jacopo (Milano University Press, 2023)
Over thirty years after the first narratives written in Italian by migrants, this book considers one of the distinctive characteristics of their writing, namely the massive presence of words and expressions in their mother tongue, which are thus kept alive in the new language and offered to Italian readers. The research is conducted on a specific corpus of 157 short stories and novels published in Italy between 1990 and 2020, written by 91 authors from 34 different countries. Over 500 words have been extracted and collected in a glossary: the abundance of graphic variants, the grammatical class adopted in Italian, the languages of origin (at least 30 ascertainable) and the most frequent semantic fields are detected. The diffusion of these migrant words is also considered as a sign of a possible lexical renewal due to the contact between Italian and migrant languages.